Influence of cognitive strategies of emotional regulation in the subjective and psychological well-being of university students - Canedo, Corel Mateo (2019)
Background: In recent years it has been proposed that cognitive strategies of emotional regulation (CSER) would have predictive capacity on different indicators of well-being, since some of them would be effective to directly increase the experience of positive emotions and lessen the negative ones. Objective: This investigation aimed to analyze the explanatory contribution of using CSER to influence the levels of subjective well-being (SWB) and psychological well-being (PWB) in university students, because this population is characterized by its particular vulnerability due to the demands of academic life. Method: Eighty-four (84) university students of the psychology program from the National University of Mar del Plata were evaluated, whose average age was 23 years old. Correlation and multiple linear regression analyses were conducted to assess the data. Results: Adaptive CSER (CSER- AD) were found to be positively associated with both types of well-being, while non-adaptive CSER (CSER-NA) did so in the opposite direction. Conclusions: This study shows the explanatory contribution of the differential use of CSER in university students’ well-being levels. The results could contribute to design health promotion and prevention programs in this population, given that feelings of well-being influence the coping skills for facing the academic demands.